2019
DOI: 10.21203/rs.2.19266/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide identification and evolutionary and expression analysis of the wheat amino acid transporter, an important gene family involved in abiotic stresses

Abstract: Background: Amino acid transporters (AATs), which transport amino acids across cellular membranes, play important roles in alleviating plant damage under stresses as well as in plant growth and development. Although this family has been systematically studied in many plant species, little is known about the AAT genes in bread wheat ( Triticum aestivum L.) due to its complex genome sequence. Results: In this study, a total of 296 AAT genes were identified from the latest wheat genome sequence (IWGSC v1.1) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…In potatoes, the StAAP1 antisense line inhibits the transport of amino acids from source organs to the phloem, leading to a signi cant reduction of amino acids in tuber (Koch et al 2003). TaAAP3, TaATLa2 and TaATLb13 are involved in the response to drought and high-temperature stresses by regulating amino acid distribution (Tian et al 2019;Tian et al 2020). However, regarding the research on foxtail millet AAPs, it has been reported that SiAAP9 is highly expressed in foxtail millet immature spikelets and seeds only through Preliminary bioinformatics and RNA-seq analysis (Yang et al 2021), but there is no indepth analysis of the functions of SiAAP9.…”
Section: Introductionmentioning
confidence: 99%
“…In potatoes, the StAAP1 antisense line inhibits the transport of amino acids from source organs to the phloem, leading to a signi cant reduction of amino acids in tuber (Koch et al 2003). TaAAP3, TaATLa2 and TaATLb13 are involved in the response to drought and high-temperature stresses by regulating amino acid distribution (Tian et al 2019;Tian et al 2020). However, regarding the research on foxtail millet AAPs, it has been reported that SiAAP9 is highly expressed in foxtail millet immature spikelets and seeds only through Preliminary bioinformatics and RNA-seq analysis (Yang et al 2021), but there is no indepth analysis of the functions of SiAAP9.…”
Section: Introductionmentioning
confidence: 99%